Energetic ion enhancements in sheaths driven by interplanetary coronal mass ejections - Kilpua Emilia; Vainio Rami; Cohen Christina; Dresing Nina; Good Simon; Ruohotie Julia; Trotta Domenico; Bale Stuart D; Christian Eric; Hill Matt; McComas David J; McNutt Ralph; et al. (SPRINGER, 2025)
We analyze here an energetic proton enhancement in a sheath ahead of a slow interplanetry coronal mass ejection (ICME) detected by Parker Solar Probe on June 30, 2021 at the heliospheric distance of 0.76 AU. The shock was likely quasi-parallel and had a high Mach number. However, the proton fluxes were not enhanced at the shock but about an hour later. The fluxes stayed elevated with a sporadic behaviour throughout the sheath. We suggest that some mechanism internal to the sheath was responsible for the energization. The observations show enhanced levels of magnetic field fluctuations in the sheath and frequent presence of highly reduced magnetic helicity structures (sigma(m)) at various time scales, representing either small-scale flux ropes or Alfvenic fluctuations that could have contributed to the energization. The correlation between the energetic proton fluxes and normalized fluctuation amplitudes/occurrence of high sigma(m) structures was generally weak or negligible. The most striking feature of the sheath was a strong enhancement of density (up to 50 cm(-3)) that implies the importance of compressive acceleration in the sheath. A statistical analysis of ion enhancements of 73 sheaths detected by ACE at ~1 AU reveals that this sheath was peculiar as in ICME-driven sheaths preceded by strong shocks the ion fluxes typically peak at the shock and strongly decline through the sheath.